2016
DOI: 10.1097/pec.0000000000000942
|View full text |Cite
|
Sign up to set email alerts
|

Performance in Trauma Resuscitation at an Urban Tertiary Level I Pediatric Trauma Center

Abstract: Primary and secondary surveys are frequently performed incompletely and inefficiently regardless of level of training or type of training program. There is no difference in measured performance among different types of residency programs. The impact of trauma resuscitation education on improved survey performance should be studied prospectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 8 publications
0
22
0
Order By: Relevance
“…A further eight studies were identified by checking the references lists. Among these 165 studies, 50 were eligible according to the inclusion criteria (online supplementary table S1),4 5 8 13 21–66 and five of these evaluated the impact of video review in regards to improvement in patient care (PICOS)8 21 23 41 62 (figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A further eight studies were identified by checking the references lists. Among these 165 studies, 50 were eligible according to the inclusion criteria (online supplementary table S1),4 5 8 13 21–66 and five of these evaluated the impact of video review in regards to improvement in patient care (PICOS)8 21 23 41 62 (figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…There were 6 cohort or case–control studies,8 21–23 27 42 27 cross-sectional studies24 25 28 30 33–40 43 44 46 47 49 51–54 56–59 65 66 and 17 case reports or series4 5 13 26 27 29 31 32 45 48 50 55 60–64 (figure 2). There were no trials or protocols of RCTs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations